Treating military sexual trauma - Katz, Lori S. (Springer Publishing Company, 2016)
Section I: Understanding military sexual trauma -- What is military sexual trauma? / Lori S. Katz -- Historical and military cultural context of military sexual trauma / Kate Majewski -- Attachment, neurobiology, and military sexual trauma / Andrei Novac -- Came to serve, left betrayed: Military sexual trauma and the trauma of betrayal / Kristen M. Reinhardt, Carly P. Smith, and Jennifer J. Freyd -- Section II: Treatments for military sexual trauma -- Affect regulation for military sexual trauma / Sheela Raja -- Military sexual trauma and treatment of sleep disorders and nightmares / Bruce Capehart and Jason DeViva -- Substance abuse, military sexual trauma, and the seeking safety model / Lisa M. Najavits and Ramya Palacholla -- Prolonged exposure and cognitive processing therapy for military sexual trauma-related posttraumatic stress disorder / Michele Bedard-Gilligan, Elizabeth Marks, Belinda Graham, Natalia Garcia, Alissa Jerud, and Lori A. Zoellner -- Treating military sexual trauma With EMDR therapy / E. C. Hurley -- Acceptance and commitment therapy: A case study for military sexual trauma / Annabel Prins, Darrah Westrup, and Robyn D. Walser -- Treating military sexual trauma with somatic experiencing / Vanessa T. Hughes and Peter A. Levine -- Healthy sexual functioning after military sexual trauma: An interview with Wendy Maltz / Wendy Maltz and Lori S. Katz -- Warrior Renew: An integrative treatment for military sexual trauma with an emphasis on interpersonal factors / Lori S. Katz -- Section III: Special issues when treating military sexual trauma -- Therapist vicarious trauma and burnout when treating military sexual trauma / Terri Spahr Nelson -- Psychotherapeutic and third-party issues when treating military sexual trauma / Jane Hammerslough